Inhibition of autophagy by 3-MA enhances endoplasmic reticulum stress-induced apoptosis in human nasopharyngeal carcinoma cells - SONG, LELE (D.A. Spandidos, 2013)
Radiotherapy and adjuvant cisplatin chemotherapy are the mainstream treatments for nasopharyngeal carcinoma (NPC), which effectively improve the outcome and reduce tumor recurrence. However, the resistance mechanism(s) involved in radiotherapy and chemotherapy, which is the main barrier in NPC treatment, remains undefined. Therefore, there is an urgent requirement for the identification of new therapeutic strategies or adjuvant drugs. In the present study, the effects of autophagy inhibitors on endoplasmic reticulum (ER) stress-induced autophagy was investigated. Combining 3-methyladenine (3-MA) with cisplatin (DDP), ionizing radiation (IR), 2-deoxy-D-glucose (2-DG) or tunicamycin (TM) resulted in enhanced cell death, as revealed by MTT and colony formation assays. Flow cytometry results demonstrated that the sensitivity of NPC cells to DDP- and IR-induced apoptosis was not significant. DDP, IR, 2-DG and TM induced ER stress and autophagy. Using fluorescence microscopy, 3-MA was identified to increase the apoptotic cell death induced by DDP, IR, 2-DG or TM. In addition, 3-MA inhibited the increased autophagy induced by DDP, IR, 2-DG or TM, as demonstrated by western blot analysis and immunocytochemistry results. Results of the present study indicate that autophagy acts as a protective mechanism response to the apoptosis induced by DDP, IR, 2-DG or TM.